Towards the E-Society
DOI: 10.1007/0-306-47009-8_7
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of Smart Card-Based Fingerprint Recognition for Secure User Authentication

Abstract: Abstract:In the modern electronic world, authentication of a person is an important task in many areas of day-to-day life. Using a biometrics to authenticate a person's identity has several advantages over the present practices of Personal Identification Number stored in smart cards. However, there is an open issue of integrating biometrics into the smart cards. Typical authenticating algorithms by using biometrics may not be executed in real-time on the resource-constrained smart cards. In this paper, we anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…To assign the verification steps to either the smart card or the card reader, we first evaluated the resource requirements of each step. Gil et al [22] reported that the preprocessing and extraction steps could not be executed in resource-constrained environments such as the smart card, so we assigned only the minutiae-matching step to the smart card.…”
Section: Fingerprint-based Match-on-cardmentioning
confidence: 99%
See 1 more Smart Citation
“…To assign the verification steps to either the smart card or the card reader, we first evaluated the resource requirements of each step. Gil et al [22] reported that the preprocessing and extraction steps could not be executed in resource-constrained environments such as the smart card, so we assigned only the minutiae-matching step to the smart card.…”
Section: Fingerprint-based Match-on-cardmentioning
confidence: 99%
“…Central storage of biometric patterns leaves the system open to misuse of the biometric patterns: for example, the Big Brother problem. To protect against misuse, the database can be decentralized into millions of smart cards [12]- [22]. Most of the current implementations of this solution accomplish the biometric verification process solely outside of the smart card.…”
Section: Introductionmentioning
confidence: 99%
“…To assign the verification steps to the USB token or the host PC, we evaluate first the resource requirements of each step. Gil et al [10] reported that the Pre-processing and Extraction steps cannot be executed on the resource-constrained environments such as USB token. Thus, we determined the Minutiae Matching step is executed on the USB token.…”
Section: Match-on-tokenmentioning
confidence: 99%
“…With the central storage of the biometric pattern, there are open issues of misuse of the biometric pattern such as the "Big Brother" problem. To solve these open issues, the database can be decentralized into millions of security token such as smart card, USB token [8][9][10]. USB token is technologically identical to smart cards, with the exception of the interface to the computer.…”
Section: Introductionmentioning
confidence: 99%
“…The login authentication schemes based on biological features use a biometric of human beings that cannot change to carry out identity authentication. It is difficult for attackers to imitate these biometrics, such as iris [22,35], fingerprint [11], face [23], and so on. Some schemes (such as fingerprint and iris authentication methods) adopt static biometric authentication, which provides attacker with opportunities to log in illegally, thus threatening people's privacy and property security.…”
Section: Introductionmentioning
confidence: 99%